Thioredoxin h2 contributes to the redox regulation of mitochondrial photorespiratory metabolism. (22nd August 2019) - da Fonseca‐Pereira, Paula; Souza, Paulo V.L.; Hou, Liang‐Yu; Schwab, Saskia; Geigenberger, Peter; Nunes‐Nesi, Adriano; Timm, Stefan; Fernie, Alisdair R.; Thormählen, Ina; Araújo, Wagner L.; Daloso, Danilo M.
Abstract: Thioredoxins (TRXs) are important proteins involved in redox regulation of metabolism. In plants, it has been shown that the mitochondrial metabolism is regulated by the mitochondrial TRX system. However, the functional significance of TRX h2, which is found at both cytosol and mitochondria, remains unclear. Arabidopsis plants lacking TRX h2 showed delayed seed germination and reduced respiration alongside impaired stomatal and mesophyll conductance, without impacting photosynthesis under ambient O2 conditions. However, an increase in the stoichiometry of photorespiratory CO2 release was found during O2 ‐dependent gas exchange measurements in trxh2 mutants. Metabolite profiling of trxh2 leaves revealed alterations in key metabolites of photorespiration and in several metabolites involved in respiration and amino acid metabolism. Decreased abundance of serine hydroxymethyltransferase and glycine decarboxylase (GDC) H and L subunits as well as reduced NADH/NAD + ratios were also observed in trxh2 mutants. We further demonstrated that the redox status of GDC‐L is altered in trxh2 mutants in vivo and that recombinant TRX h2 can deactivate GDC‐L in vitro, indicating that this protein is redox regulated by the TRX system. Collectively, our results demonstrate that TRX h 2 plays an important role in the redox regulation of mitochondrial photorespiratory metabolism. Abstract : Overall, our results suggest that TRX h 2 plays an important role in the redox regulation of metabolism and that the lack of TRX h2 leads to a reprograming of the mitochondrial photorespiratory metabolism in Arabidopsis thaliana .